Faktor-Faktor yang Mempengaruhi Produksi Subsektor Tanaman Pangan di Provinsi Jawa Timur: Factors Affecting the Production of the Food Crop Subsector in East Java Province - Prince Charles Heston Runtunuwu; Fahima Nasar; Fahmi Tanjung (Society, 2022)
This study aims to analyze the factors that influence the food crop subsector production. This research paper used the panel regression analysis method to analyze the secondary data. The findings indicated that agricultural lands, laborers, fertilizer subsidies, rainfall, and irrigation infrastructure partially increase the production of the food crop subsector.